AMERICAN SENTIMENT, The Case of Muslim Student Activists in Makassar - Syamsul Arif Galib (JICSA : Journal of Islamic Civilization in Southeast Asian, 2017)
The main objective of this paper is to identify how the anti-American sentiment emerges among the Muslim student activists at university. This paper tries to figure out the reason why America perceived negatively how the actions of the activists which are considered as the attempt against America. It verifies that the spirit of anti America occurs among the Muslim students. However, this study reveals that the tendency of anti-America is not related to a religious motive but related to other motives such as American close relationship with Israel, American foreign policy, cultural westoxification and America as a symbol of global capitalism.The respondents for this study were taken from the Islamic activists’ organizations such as Muslim Student Association (HMI), Indonesian Muslim Student Action Union (KAMMI), Indonesian Islamic Students Movement (PMII), and The Student Movement of Liberation (Gema Pembebasan) which located in Makassar.